Penegakan Hukum Tindak Pidana Perikanan Oleh Kapal Perang Republik Indonesia - Ketut Darmika (Universitas Jayabaya, 2015)
Illegal fishing is a serious problem that must be addressed because it is very harmful to the preservation of resources and economically detrimental for the country. This illegal activity has directly violated the provisions of Law No. 45 Year 2009 on the Amendment Law No. 31 of 2004 about Fisheries. The method used in this study is a legal normative juridical research conducted in an attempt to obtain the necessary data regards to the issues. The data used are secondary data consists of primary legal materials, secondary law and tertiary legal materials. In addition, it is also used as the primary data supporting secondary data of law materials. For data analysis was conducted using qualitative analysis. From the research results can be concluded that the act of shooting or sinking and exterminating evidence of foreign-flagged fishing vessels that sufficient evidence of a criminal act fisheries in WPP RI in practice can be done by means of hot pursuit, in the process of investigation and carry out the determination of the court.